(untitled) (Journal of the College of Basic Education, 2022)
Praise be to God who taught by the pen, taught man what he did not know, the Creator of everything, the All-Hearing, the All-Knowing, He created man after he was nothing and was not a thing mentioned. I chose the subject of the stages of embryonic development because of its importance, and the need for man to know how he was created. The grace of creation that God created in man requires pause and reflection, and how God created His creation and others in the best and most beautiful way... Therefore, I decided to shed light on this important topic, which focuses on one of the topics of scientific miracles, which is the stages of embryo development in the Holy Qur’an and the Sunnah of the Prophet, and to prepare it in six topics as follows: The first topic: the concept of the fetus and its preservation in Islam, and it had two demands: The first: defining the fetus linguistically and idiomatically. The second: Preserving the fetus in Islam.